Pengenalan Algoritma Dengan Menggunakan Aplikasi Scratch Jr Di SMAN 1 Pemenang Lombok Utara - Umar Abdullah; Muhammad Khair Syawaludin; Khairatun Hisan; Dimas Indrawadi; Siti Indah Rohiana; Jannatul Ma'wa; Rabbelia Qudrani; Sefti Fajriatul Musyarrofah; Haeva Apriliana; I Gede Adhitya Wisnu Wardhana; Fariz Maulana (Sinergi dan Harmoni Masyarakat MIPA, 2025)
This community service program aimed to introduce fundamental algorithmic concepts to high school students using a visual, interactive approach through the Scratch Jr application. The activity took place at SMAN 1 Pemenang, North Lombok, as part of the MBKM program by mathematics students of Universitas Mataram. This initiative responded to the growing need for computational thinking and logical reasoning as key skills in 21st-century education. The program involved a series of stages: preparatory meetings, delivery of instructional materials, and hands-on practice. A pre-test and post-test were administered to measure students’ understanding before and after the activity. Statistical analysis using a paired sample t-test in SPSS revealed a significant improvement in students' scores (mean pre-test: 5.81; post-test: 9.06; p < 0.001), demonstrating the effectiveness of the Scratch Jr-based learning method. These findings emphasize the potential of visual programming tools to enhance students’ logical reasoning and computational literacy. The success of this activity also suggests the importance of integrating digital technology in classroom instruction and the value of teacher training in using such tools.